THE MEDIATING ROLE OF BRAND KNOWLEDGE IN THE INFLUENCE OF ADVERTISING APPEAL ON THE INTENTION TO USE SERVICES - Komang Amanda Jaya; I Gst. A. Kt. Gd. Suasana (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to analyze the mediating role of brand knowledge in the influence of advertising appeal on the intention to use services among prospective customers of Dins Beauty Lounge Salon in Denpasar City. A quantitative approach was employed using a non-probability sampling technique with purposive sampling applied to 120 respondents. Data were collected through a survey using questionnaires and analyzed using path analysis and the Sobel test. The results reveal that advertising appeal has a significant effect on both brand knowledge and purchase intention. Additionally, brand knowledge significantly influences purchase intention and partially mediates the relationship between advertising appeal and purchase intention.